Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/cancers13112569
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Patterns Found in the Nuclear Localization Signals (NLSs) Associated with EBV-1 and EBV-2 Provide New Insights into Their Contribution to Different Cell-Type Specificities

Abstract: The Epstein–Barr virus (EBV) is a globally dispersed pathogen involved in several human cancers of B-cell and non-B-cell origin. EBV has been classified into EBV-1 and EBV-2, which have differences in their transformative ability. EBV-1 can transform B-cells into LCL more efficiently than EBV-2, and EBV-2 preferentially infects T-cell lymphocytes. The EBNA3A oncoprotein is a transcriptional regulator of virus and host cell genes, and is required in order to transform B-cells. EBNA3A has six peptide motifs call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
(91 reference statements)
0
4
0
Order By: Relevance
“…So far, two major EBV types, named type 1 and type 2 EBV, with nearly identical genomes except for the genes encoding some of the nuclear proteins, the EBV nuclear antigen (EBNA)-2 and EBNA-3A, -3B and -3C, have been identified [8,9]. Type 1 EBV is found ubiquitously worldwide and has a higher transformation efficiency of B cells, while type 2 EBV is mainly detected in Africa [10,11]. Primary infection mostly involves asymptomatic children prior to the age of 5 years and is rather rare in adults who more frequently acquire severe symptoms called infectious mononucleosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…So far, two major EBV types, named type 1 and type 2 EBV, with nearly identical genomes except for the genes encoding some of the nuclear proteins, the EBV nuclear antigen (EBNA)-2 and EBNA-3A, -3B and -3C, have been identified [8,9]. Type 1 EBV is found ubiquitously worldwide and has a higher transformation efficiency of B cells, while type 2 EBV is mainly detected in Africa [10,11]. Primary infection mostly involves asymptomatic children prior to the age of 5 years and is rather rare in adults who more frequently acquire severe symptoms called infectious mononucleosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Zanella, L. et al [ 1 ] evaluated more than a thousand EBNA3A sequences of EBV from different human clinical manifestations and geographic locations and found differences in six peptide motifs called nuclear localization signals (NLSs) among the EBV types. EBNA3A from EBV-2 showed that two (NLS3 and NLS4) of the six NLSs were altered (non-canonical) compared with the EBNA3A EBV-1.…”
Section: Ebv-encoded Genesmentioning
confidence: 99%
“…The EBV genome encodes more than 85 genes, which are involved in the pathogenesis of infection and initiating EBV-associated human disease. There are two major types of EBV: type 1 EBV, which is found worldwide, and type 2 EBV, which is mainly detected in Africa [ 3 ]. EBV is the most frequent cause of infectious mononucleosis, with primary infections commonly occurring asymptomatically in teenagers and young adults, especially college students, while in adults, the symptoms are more severe.…”
Section: Introductionmentioning
confidence: 99%